Perancangan Desain Kemasan Corona Kit Package - Sri Ocha Ayu Lestari sri (Publikasi Indonesia, 2022)
Currently, the development of packaging design in Indonesia continues to experience a significant increase, especially in products that are used daily such as various types of packaging circulating in supermarkets ranging from basic and non-basic needs such as starter kits, and slowly design activities are starting to be glimpsed into one of the most influential things in product marketing. The purpose of this research is to create functional, attractive and creative corona kit packaging to attract consumers' attention. The method used in this study is a qualitative method consisting of pre-production, production, and post-production stages. The packaging design for the Corona Kit Package was designed using the Dispenser Box Pettern and Die-Cut Box techniques. Corona Kit This package contains a medical mask, hand sanitizer and antiseptic wipes as the most important health protocol.With a creative strategy, of course, the production process can run optimally and get the expected goals